Density Functional Theory Study of the Catalytic Reaction of $N_2O(^1\sum)$ with $CO(^1\sum^+)$ by $Ni^+$ (Journal of Atomic and Molecular Sciences, 2014)
The mechanism of the cyclic reaction $CO(C_{∞ v}, ^1\sum^+) + N_2O(C_{∞ v}, ^1\sum^+) → N_2(D_{∞ h}, ^1\sum^+_g)+ CO_2(D_{∞ h},^1\sum^+_g)$ catalyzed by $Ni^+$ has been investigated on both doubleand quartet potential energy surfaces (PESs). The reactions were studied by theUB3LYP density functional theory. The calculated results of different spin PES showthat the reaction proceeds in a two-step manner and spin crossing between differentPES occurs. The involved crossing between the PES has been discussed by means ofthe intrinsic reaction coordinate approach used by Yoshizawa et al., and the crossingpoints were located. Furthermore, the spin-orbit coupling (SOC) is calculated betweenelectronic states of different multiplicities at the crossing points to estimate the intersystemcrossing probabilities.
Keywords: density functional theory; crossing point; molecule orbital(MO); natural bond orbital (NBO); spin-orbit coupling (SOC).